GEOTHERMAL ENERGY & URBAN -RURAL EQUILIBRIUM OF SOUTHEAST EUROPE, SOUTHEAST SERBIA, REGIONAL FOCUS ON NIS SURROUNDING - Jovanovic, Aleksandar LJ; Cekic, Nikola (Arhitektura i urbanizam, 2017)
Тhe surrounding of Nis has been known for various geothermal manifestations. The city itself has direct use of Nis Spa, where couple of balneological purposes and heating systems have been installed. However, other local resources in Nis surrounding are little known. Also, Sokobanja has a long history of thermal waters ‘use throughout its rich history, from the Antique throughout the middle ages and Turkish rule. This is also present in towns of Bela Palanka and Svrljig in South-East Serbian region surrounding Nis. These resources can be used for supplying the cities and villages with heat in the future. More importantly, communities in local towns in the region can be supported by more proficient use of geothermal potentials, as this idea supports the alleviated concentration of inhabitants in the region. It supports local renewable energy sources and a greater ration between potentials and actual use of geothermal sources, which tends to be very low in Serbian cities and rural places. In this paper, these resources are going to be presented, for the community in Serbia to have an insight and to be reminded of its potentials and significance for regional development and local resource utilization. Built heritage and urban-architectural wholes in some of these towns and in the villages, are neglected and geothermal resources in their vicinity underused. A more organized use of geothermal potentials can lead to their regenerations. It can support the idea of a more balanced rural-urban development of the region of Nis. However, geothermal energy can also be beneficial for future regional energy planning and cooperation between towns and villages in South-Eastern Serbian regions like Nis region. And this can be an important strategy in regional planning and energy planning for the future, once the economic crisis would stop to prevail in Serbia. The authors of this paper point out to the long-term planning opportunity of Nis region, once geothermal energy is made more accessible and the constraints, being mostly of financial nature, however of societal nature, are minimized. The problem of the equilibrium between the city and its surrounding rural places can be made through the local resource´s utilization, such as geothermal, where this can be applicable or in combination with other renewable sources available at the locale (solar, biomass etc.). It is of great importance that the regions in Serbia cooperate in terms of geothermal energy planning. Various studies in Vojvodina are beneficial for Nis region. On the example of Reykjavik in Iceland, one can draw lessons on urban sprawl that has been influenced by the abundance of energy. Nis as a city is characterized by urban sprawling and environmental burden created by fossil fuel use and this can be further mitigated by utilizing geothermal and more importantly, strategic rural-urban planning with the existing geothermal resources. A change for the individual user still must make a “break-through” for renewable energy to “pay off”. In terms of geothermal application in rural places, there is a question of densities of the end users, that still should be tackled as a problem in the future of urban planning for the Nis region.